2015
DOI: 10.1097/mib.0000000000000538
|View full text |Cite
|
Sign up to set email alerts
|

Different Profile of Efficacy of Thiopurines in Ulcerative Colitis and Crohnʼs Disease

Abstract: Thiopurines are effective in maintaining steroid-free CR in both UC and CD although they show a better profile of efficacy in terms of MH in cases of UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Here, Mayo 0 was defined as endoscopic remission (normal mucosa), Mayo 1 as mild disease activity (erythema, decreased vascular pattern, mild friability), Mayo 2 as moderate disease activity (marked erythema, lack of vascular pattern, friability, erosions) and Mayo 3 as severe disease activity (spontaneous bleeding and ulceration). For the purpose of analysis, categories from both endoscopy scores of CD (SES-CD) and UC (Mayo endoscopic subscore) were merged on categorical level of mucosal damage (0–3) to finally create an IBD composite endoscopy score (27).…”
Section: Methodsmentioning
confidence: 99%
“…Here, Mayo 0 was defined as endoscopic remission (normal mucosa), Mayo 1 as mild disease activity (erythema, decreased vascular pattern, mild friability), Mayo 2 as moderate disease activity (marked erythema, lack of vascular pattern, friability, erosions) and Mayo 3 as severe disease activity (spontaneous bleeding and ulceration). For the purpose of analysis, categories from both endoscopy scores of CD (SES-CD) and UC (Mayo endoscopic subscore) were merged on categorical level of mucosal damage (0–3) to finally create an IBD composite endoscopy score (27).…”
Section: Methodsmentioning
confidence: 99%
“…Both agents have proven efficacy in the treatment of Crohn's disease (CD) and ulcerative colitis (UC). 4 7 Unfortunately, the use of thiopurines is frequently accompanied by side effects such as hepatotoxicity, gastrointestinal complaints, and flu-like symptoms or leukopenia, often leading to premature treatment discontinuation. 8 , 9 …”
mentioning
confidence: 99%
“…Thiopurine is more effective in maintaining mucosal healing in UC than in CD. 18 Thiopurine is the key drug for maintaining remission of UC, and at our institution, thiopurine is mainly used in combination with mesalazine. In this study, the cumulative non-relapse rates of UC patients with C/C and C/T genotypes were compared to assess the long-term efficacy of thiopurine for maintenance therapy.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Previous reports have shown that only about 20% of patients treated with thiopurine sustain mucosal healing after 2 years. 18 At our institution, thiopurine, in combination with infliximab (IFX) is mainly used to maintain remission in patients with CD. We calculated long-term cumulative surgery-free rates without change of therapy between CD patients with C/C and C/T genotypes treated with combination therapy and observed no significant difference between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%